Z historii rodziny leksykalnej rzeczownika paskuda - Krótki, Zuzanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2017)
In the article the lexical units gathered from all history of Polish language were put under investigation belonging to the word family of the noun – paskuda. By using the semasiological method the researched process of how particular formations formed the new semantical senses manifested itself and how eradicated the old ones. The general key of its movings and the purpose were underlined and of these modifications ‘in the better serving’ depicted. As shown the afore-mentioned lexical units comprised with a multitude of senses already by-gone featuring the adultery, the burglary, defamation, gluttony and the cattle disease. At the beginning they seemed stable nevertheless the overuse of them paradoxically caused the eradication of popular meanings. They were not forgotten fully because it’s ‘residua’ were found in folk-slang. The essential figure is hereditary of pre-Slavic senses for instance; ‘something shoddy<poor>’, ‘something off’, ‘something repulsive’. Nowadays they function primarily in written material of all lexical family of the noun – paskuda.